Non-constant coefficient friction models in 3d simulation of drawing processes - Rańda, Jacek; Colville, Kevin W.; Mahrenholtz, Oskar (Computer Assisted Methods in Engineering and Science, 2001)
Different friction models: the classic one proposed by Amontons- Coulomb (AC) with a constant friction coefficient, a three-parameter model proposed by Wriggers et al. [9], and a model based on the concept of 'work-hardening' proposed by de Souza Neto et al. [8], are applied to the 3-D square-cup drawing and S-rail stamping FE simulations. The benchmark problems used during NUMISHEET'93 for a cup drawing and NUMISHEET'96 for S-rail stamping were simulated here. The results obtained for these three models are presented to illustrate the influence of the friction model on the drawing process.